The eConnect and learn curriculum change in Trinidad and Tobago : the voice of the teacher - Mitchell, Beular (2012)
Takes the form of a qualitative case study and seeks to examine the concerns of eight teachers, in the St. Patick Educational District in the south of Trinidad, about the implementation of the eCal initiative and to explore factors influence their concerns.